Utilizing Facebook in Developing UMKM Business Networks Based on Big Data - muhammad raihan; Muhammad Raihan; Muhammad Ryan Akbar; Reza Aprilliyan; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
In this digital era, leveraging social media platforms such as Facebook holds significant potential for developing the business networks of Micro, Small, and Medium Enterprises (UMKM). Facebook provides a vast platform for UMKM to expand their market reach. One innovative approach is the use of Big Data in marketing strategies and business network development. By analyzing data obtained from user interactions on Facebook, UMKM can identify consumer patterns and preferences, enabling them to formulate more effective and personalized marketing strategies. This research also discusses various tools and techniques that can be used to process and analyze big data, as well as case studies on the application of big data in the development of UMKM business networks on the Facebook platform.